Pengaruh Perbedaan Lama Penyimpanan pada Refrigerator terhadap pH Putih Telur, Indeks Putih Telur, dan Nilai Haugh Unit Telur Ayam Ras Herbal. - Sari, Siska Patika; Nova, Khaira; Septinova, Dian; Riyanti, Rr (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2025)
This research aimed to determine the effect of differences in storage time for herbal chicken eggs in the refrigerator on egg quality, which includes egg white pH, albumen index, and haugh unit value and knowing the storage time that can maintain the quality of herbal chicken eggs in the refrigerator. This research was conducted out on January--March 2024, at Kampung Baru, Kedaton, Bandar Lampung as a place to store eggs during research and in the Animal Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung as a place for collecting research data. This research used a Completely Randomized Design (CRD) with 4 treatments of herbal egg storage time for 0, 12, 24, 36 days and 5 replications. In each treatment, 25 herbal eggs were used, with a total of 100 herbal eggs used with an average weight of 58,6±3,97 g. The data obtained were by tested using analysis of variance. If there is a real effect, the Least Significant Difference Test (LSD) is carried out at the 5% level. The result of this study showed that herbal egg storage time treatment had a significant effect (P<0.05) on the haugh unit value, albumen index, and egg white pH. In this reserch, storing herbal chicken eggs for 36 days in the refrigerator produced the lowest haugh unit value (65.08), the lowest albumen index (0.060), and the highest egg white pH (8.94), but still in good quality.